Strengths and limitations of coronary angiography with turbo high-pitch third-generation dual-source CT. Issue 9 (September 2017) - Ochs, M.M.; Andre, F.; Korosoglou, G.; Fritz, T.; Seitz, S.; Bogomazov, Y.; Schlett, C.L.; Sokiranski, R.; Sommer, A.; Gückel, F.; Brado, M.; Kauczor, H.-U.; et al.
Abstract : Aim: To define practical limitations of diagnostic image quality for recently introduced turbo high-pitch scan mode (THP) in third-generation dual-source computed tomography (CT). Materials and Methods: Two hundred and twenty-nine consecutive patients undergoing CT coronary angiography were included in this retrospective single-centre analysis. A contrast-enhanced volume dataset was acquired in THP. Image quality of coronary segments was classified as diagnostic or non-diagnostic by three blinded readers. Segments were stated as non-diagnostic if at least one of three readers could neither exclude nor confirm significant stenoses. Multivariable logistic regression was used to assess relationships between number of non-diagnostic segments and common influencing factors. Results: Median effective radiation dose was 0.6 (interquartile range [IQR], 0.4–0.8) mSv overall and 0.3 (IQR, 0.3–0.4) mSv in the 70 kV subgroup of this middle aged, predominantly pre-obese cohort (age: 61 [IQR, 52–67] years; body mass index [BMI]: 26 [IQR, 23–29] kg/m 2 ) with a low–moderate median Agatston score (AS) 0 (IQR, 0–70). Diagnostic image quality was found in 98.1% of 3, 678 coronary segments. AS was independently associated with diagnostic image quality ( B =0.34; p =0.02), whereas heart rate, BMI, and presence of arrhythmia were not. The portion of diagnostic coronary segments decreased slightly in obese patients with heart rates >65 beats/min and dropped significantly in patients with an AS >600 ( p =0.003). Conclusion: THP enables CT coronary angiography with minimal radiation exposure and is most appropriate in non-obese patients with stable sinus rhythm ≤65 beats/min and a calcium score ≤600. Highlights: Turbo high-pitch scanners were recently introduced for coronary CT angiography. THP is most appropriate in sinus rhythm ≤65bpm, BMI <30kg/m 2, Agatston ≤600. Selection criteria to optimize radiation exposure and image quality.